DARK MATTER IN THE CENTRAL REGION OF THE SPIRAL GALAXY NGC4321 - Ali, I. A. M; Hwang2, C. -Y; Abidin, Z. Z (university of eloued -جامعة الوادي, 2019)
We present our results of 12 CO(1-0) transition in the central region of NGC 4321 using the Atacama Large Millimeter and Sub-millimeter Array (ALMA). We found an unaccounted mass of 2.3×109 Mʘ within the central 0.7 kpc of this galaxy. The expected mass of the supermassive black hole (SMBH) in this galaxy is much smaller than the unaccounted mass. The invisible mass is likely caused by dark matter in the central region of the galaxy, indicating a cuspy dark matter profile. We also investigated the Modified Newtonian Dynamics (MOND) as an alternative mechanism to explain the invisible mass. We noted that at the radius of 0.7 kpc of the galaxy, the acceleration is about 1.04×10-7 cm s-2, which is much larger than the critical acceleration a0 ~1.2×10-8 cm s-2 in the MOND theory, suggesting that theory might not be able explain the unseen mass problem in central region of this galaxy
ARTICLE
Keywords: cosmology; dark matter; galaxy.